2023
DOI: 10.2903/j.efsa.2023.8006
|View full text |Cite
|
Sign up to set email alerts
|

Scientific opinion on the tolerable upper intake level for vitamin B6

Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver a scientific opinion on the tolerable upper intake level (UL) for vitamin B6. Systematic reviews of the literature were conducted by a contractor. The relationship between excess vitamin B6 intakes and the development of peripheral neuropathy is well established and is the critical effect on which the UL is based. A lowest-observed-effect-level (LOAEL) could not be establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 154 publications
1
3
0
1
Order By: Relevance
“…The authors suggested that, considering the consumption of a 10 g serving of fresh microgreens, these concentrations could be appropriated according to the recommended daily Se allowance (RDA) of 55 μg• day −1 in adults (70 kg body weight) and taking into consideration that less than 55 μg• day −1 results in a deficiency level and more than 400 μg day −1 of results in toxicity. 1,5 In that sense, it could be said that the Se accumulated in the microgreens reported in our work is within the safe range of Se intake.…”
Section: Plant Yield and Selenium Concentrationsupporting
confidence: 60%
See 1 more Smart Citation
“…The authors suggested that, considering the consumption of a 10 g serving of fresh microgreens, these concentrations could be appropriated according to the recommended daily Se allowance (RDA) of 55 μg• day −1 in adults (70 kg body weight) and taking into consideration that less than 55 μg• day −1 results in a deficiency level and more than 400 μg day −1 of results in toxicity. 1,5 In that sense, it could be said that the Se accumulated in the microgreens reported in our work is within the safe range of Se intake.…”
Section: Plant Yield and Selenium Concentrationsupporting
confidence: 60%
“…The recommended Se dietary intake for humans varies depending on age group and other factors (15− 40 μg day −1 for ages from 1 to 13 years old, 55 μg day −1 from 14 to 50 years old, and 60−70 μg day −1 above 51 years old and for pregnant women or during breastfeeding). 1 Unfortunately, around a billion people worldwide are affected by Se deficiency. The low Se status is associated with a wide range of pathological conditions such as Keshan disease, mood disorders, reduced male fertility, enhanced susceptibility to infections, and disturbance of thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…Cessation of multivitamins and energy drinks led to a complete reversal of the patient's symptoms [4]. In 2023, the European Food Safety Administration (EFSA) was requested to deliver a scientific opinion on the safety of vitamin B6, which led to the establishment of a new UL of 12 mg/day [10].…”
Section: Discussionmentioning
confidence: 99%
“…revealed that lycopene can decrease the expression of proteins such as NLRP3, Pro-Caspase-1, Caspase-1, and NF-κB in the liver; decrease the abundance of Lachnospiraceae_NK4A136_group , Desulfovibrio , and Alistipes in the gut microbiota; and increase the abundance of Allobaculum microbiota, thereby increasing the content of SCFAs, inhibiting the NF-κB/NLRP3 inflammatory pathway, and ameliorating nonalcoholic fatty liver disease (NAFLD). However, intake of beta carotene has been a question worth exploring, with studies concluding that 20 mg/day or more beta carotene is contraindicated for heavy smokers; the Panel on Nutrition, Dietetic Products, Novel Food and Allergy of the Norwegian Scientific Committee for Food Safety has set a tentative upper limit (TUL) of 4 mg/day for beta carotene supplementation; and the Panel on Vitamins and Minerals has set a safe upper limit of 7 mg/day for lifetime beta carotene supplementation for the general population (excluding smokers) and has discouraged concomitant use of beta carotene supplements by smokers [ 155 ].…”
Section: Natural Compounds That Regulate Glucolipid Metabolismmentioning
confidence: 99%